Was there a skills shortage in Australia? - P. N. (Raja) Junankar (Institute for the Study of Labor (IZA), 2009)
The paper analyses the problem of a skills shortage in Australia. It begins with an analysis of the operation of a labour market in terms of stocks and flows of labour services and human capital acquisition. It discusses the definition of a skills shortage, why it persists, and then looks at evidence from Australia, in particular, the resource rich states of Queensland and Western Australia over the past decade. It discusses possible employer responses to a skills shortage. Finally, it discusses whether the government should intervene, and if so what policies may help to relieve a skills shortage.
Keywords: J24; J31; J48; 330; Skill shortages; wage adjustments; migrants; Qualifikation; Berufsbedarf; Lohn; Arbeitsmarkt; Wirtschaftliche Anpassung; Migranten; Australien